Microbial Community Structure and Metabolic Function in the Venom Glands of the Predatory Stink Bug, Picromerus lewisi (Hemiptera: Pentatomidae) - Jinmeng Li; Xu Tian; Tom Hsiang; Yuting Yang; Caihua Shi; Hancheng Wang; Wenhong Li (Insects, 2024)
The predatory stink bug, Picromerus lewisi (Hemiptera: Pentatomidae), is an important and valuable natural enemy of insect pests in their ecosystems. While insects are known to harbor symbiotic microorganisms, and these microbial symbionts play a crucial role in various aspects of the host’s biology, there is a paucity of knowledge regarding the microbiota present in the venom glands of P. lewisi. This study investigated the venom glands of adult bugs using both traditional in vitro isolation and cultural methods, as well as Illumina high-throughput sequencing technology. Additionally, the carbon metabolism of the venom gland’s microorganisms was analyzed using Biolog ECO metabolic phenotyping technology. The results showed 10 different culturable bacteria where the dominant ones were Enterococcus spp. and Lactococcus lactis. With high-throughput sequencing, the main bacterial phyla in the microbial community of the venom glands of P. lewisi were Proteobacteria (78.1%) and Firmicutes (20.3%), with the dominant bacterial genera being Wolbachia, Enterococcus, Serratia, and Lactococcus. At the fungal community level, Ascomycota accounted for the largest proportion (64.1%), followed by Basidiomycota (27.6%), with Vishniacozyma, Cladosporium, Papiliotrema, Penicillium, Fusarium, and Aspergillus as the most highly represented fungal genera. The bacterial and fungal community structure of the venom glands of P. lewisi exhibited high species richness and diversity, along with a strong metabolism of 22 carbon sources. Functional prediction indicated that the primary dominant function of P. lewisi venom-gland bacteria was metabolism. The dominant eco-functional groups of the fungal community included undefined saprotroph, fungal parasite–undefined saprotroph, unassigned, endophyte–plant pathogen, plant pathogen–soil saprotroph–wood saprotroph, animal pathogen–endophyte–plant pathogen–wood saprotroph, plant pathogen, and animal pathogen–endophyte–epiphyte–plant pathogen–undefined saprotroph. These results provide a comprehensive characterization of the venom-gland microbiota of P. lewisi and demonstrate the stability (over one week) of the microbial community within the venom glands. This study represents the first report on the characterization of microbial composition from the venom glands of captive-reared P. lewisi individuals. The insights gained from this study are invaluable for future investigations into P. lewisi’s development and the possible interactions between P. lewisi’s microbiota and some Lepidopteran pests.